Pengenalan Teknik Dasar Fotografi - Gunawan, Agnes Paulina (Humaniora, 2013)
These days, development in camera has become very fast and has made the society easier to develop photography as their hobbies. This can happen especially with the digital era that does not need time to process the films and to print the photos. Nowadays, photographers just need to shoot, check the results, and delete them if they are not satisfied with the outcome, or, they can save them when the pictures meet their expectations. Basically, this really has made both advanced and amateur photographers easy to work better. However, if the user does not completely understand the basic exposure techniques in photography, then it will be such a pity. They will not be able to explore the techniques that can be maximized and used to have the alternatives when it comes to working in the field. By learning these techniques, photographers can make use of the background, surroundings, and the activities of the objects, in order to achieve variations and creativity in the outcome. This is possible when they have mastered and maximized the use of diaphragm, shutter speed, ISO, and all other techniques that can be formed using these basics features.